Fluorescent nanodiamonds encapsulated by Cowpea Chlorotic Mottle Virus (CCMV) proteins for intracellular 3D-trajectory analysis. Issue 28 (29th June 2021) - Wu, Yingke; Cao, Shuqin; Alam, Md Noor A; Raabe, Marco; Michel-Souzy, Sandra; Wang, Zuyuan; Wagner, Manfred; Ermakova, Anna; Cornelissen, Jeroen J. L. M.; Weil, Tanja
Abstract : Fluorescent nanodiamonds are stabilized by a corona of virus capsid proteins. Intracellular diffusion studies were performed suggesting that virus-coated nanodiamonds could be attractive tools for conceptual understanding of cell-virus interactions. Abstract : Long-term tracking of nanoparticles to resolve intracellular structures and motions is essential to elucidate fundamental parameters as well as transport processes within living cells. Fluorescent nanodiamond (ND) emitters provide cell compatibility and very high photostability. However, high stability, biocompatibility, and cellular uptake of these fluorescent NDs under physiological conditions are required for intracellular applications. Herein, highly stable NDs encapsulated with Cowpea chlorotic mottle virus capsid proteins (ND-CP) are prepared. A thin capsid protein layer is obtained around the NDs, which imparts reactive groups and high colloidal stability, while retaining the opto-magnetic properties of the coated NDs as well as the secondary structure of CPs adsorbed on the surface of NDs. In addition, the ND-CP shows excellent biocompatibility both in vitro and in vivo . Long-term 3D trajectories of the ND-CP with fine spatiotemporal resolutions are recorded; their intracellular motions are analyzed by different models, and the diffusion coefficients are calculated. The ND-CP with its brilliant optical properties and stability under physiological conditions provides us with a new tool to advance the understanding of cell biology, e.g., endocytosis, exocytosis, and active transport processes in living cells as well as intracellular dynamic parameters.